ANALISIS PENGENDALIAN KUALITAS PRODUK GIBOULT MENGGUNAKAN METODE NEW SEVEN TOOLS DI PT ANEKA ADHILOGAM KARYA - Arera, Ardi Fian Arera Fian; Suseno, Suseno (Universitas Gajah Putih, 2023)
ABSTRACT PT Aneka Adhilogam Karya is a company located on Jl. header Batur Jaya, Batur, Tegalrejo, Kec. Ceper, Kab. Klaten, Central Java 57465. The company is a metal casting industry manufacturing/manufacturing, specifically a manufacturer of pipe connection equipment for drinking water/pressurized similar fluids and a manufacturer of drainage system components. One of them is the Gibol product, the problem with this company is that there are still a large number of defective and rejected products during the production process. Based on data obtained from PT Aneka Adhilogam Karya, it shows that there are many product defects that occur, to be precise in 2022 with a total number of repairs of 121 defective products, namely in the kropos category, total defects 20, percentage of defects 16.53%, continuous total defects 34, percentage of total defects. defect 28.10%, incomplete defect 41 percentage of total defects 33.90%, total defect table 26 percentage of total defects 21.50%. With product defects that occur, quality control is needed, namely by using the New Seven Tools method. By using 7 (Seven) data processing steps including Affinity Diagrams, Ship Relationship Diagrams, Tree Diagrams, Matrix Diagrams, Matrix Data Analysis, Arrow Diagrams, and Process Decision Program Charts. Get some problems, namely in the category of human factors the operator does not work according to the SOP, the operator is negligent, lack of communication. The method categories are mold pattern design, metal material composition, smelting process, pouring process, inlet and riser channel arrangement. The environmental categories are flying dust, the noisy work area reaches 98 dB with a noise standard of 85 dB, the hot work area reaches 31°C - 35°C. The engine category is the occurrence of problems with the smelting machine, lack of machine maintenance. By doing data processing to get control results, namely by setting up machines, improving the performance of human resources and methods, improving the environment, maintaining machines, replacing tools with new ones, conducting operator training, adding blowers. Keryword: Product Defects, Gibol, Quality, New Seven Tools